Psychogenic orofacial pain: literature review, development of a diagnostic questionnaire and three cases report. - Molina, Omar Franklin; Santos, Zeila Coelho; e Silva, Natalia de Paula; Gama, Karla Regina; Marchezan, Rogério Ferreira; Cury, Sérgio Elias; Dib, Jamil Elias (Cadernos UniFOA, 2017)
Objectives: Review the literature on psychogenic face or head pain, develop a diagnostic questionnaire for psychogenic head and face pain and present three clinical cases presenting psychogenic pain. Material and Methods: Review of 18 papers on psychogenic pain to develop a diagnostic questionnaire with questions to be answered by patients that presented these three clinical cases. Results: The common things observed in three patients presenting psychogenic pain were higher scores in bruxing behavior, depression, somatization, severe pain and the presence of psychic conflict. Conclusions: Various types of other face and headaches occur in subjects with psychogenic face and head pain. Psychogenic pain individuals usually present severe pain associated with depression. Psychic conflict, somatization and depression are usually associated with psychogenic pain.